A programmable microfluidic platform for multisample injection, discretization, and droplet manipulation - Babahosseini, Hesam (Biomicrofluidics, 2020)
A programmable microfluidic platform enabling on-demand sampling, compartmentalization, and manipulation of multiple aqueous volumes is presented. The system provides random-access actuation of a microtrap array supporting selective discretization of picoliter volumes from multiple sample inputs. The platform comprises two interconnected chips, with parallel T-junctions and multiplexed microvalves within one chip enabling programmable injection of aqueous sample plugs, and nanoliter volumes transferred to a second microtrap array chip in which the plugs are actively discretized into picoliter droplets within a static array of membrane displacement actuators. The system employs two different multiplexer designs that reduce the number of input signals required for both sample injection and discretization. This versatile droplet-based technology offers flexible sample workflows and functionalities for the formation and manipulation of heterogeneous picoliter droplets, with particular utility for applications in biochemical synthesis and cell-based assays requiring flexible and programmable operation of parallel and multistep droplet processes. The platform is used here for the selective encapsulation of differentially labeled cells within a discrete droplet array.